Dual Circularly Polarized Omnidirectional Antenna with Slot Array on Coaxial Cylinder - Bin Zhou; Junping Geng; Zhe Li; Wenzhi Wang; Xianling Liang; Ronghong Jin (International Journal of Antennas and Propagation)
A dual circularly polarized (CP) omnidirectional antenna based on slot array in coaxial cylinder structure is presented in this paper. It is constructed by perpendicular slot pairs around and along the axis of the coaxial cylinder to realize the omnidirectional CP property, and two ports are assigned in its two sides as left hand circularly polarized (LHCP) port and right hand circularly polarized (RHCP) port, respectively. The proposed antenna achieves a bandwidth of 16.4% ranging from 5.05 to 5.95 GHz with an isolation higher than 15 dB between the two CP ports, and the return loss (RL) is higher than 10 dB within the bandwidth in both of the two ports. From the measured results, the average axial ratio (AR) of the proposed antenna in omnidirectional plane is lower than 1.5 dB.